The SuratKu Application as Electronic Mail Innovation in Supporting Governance at the Kulon Progo Regency Communication and Information Office - Ach. Apriyanto Romadhan; Switsa Cellindita; Iradhad Taqwa Sihidi; Asep Nurjaman; Muhammad Kamil (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This study focuses on the